Pengenalan Data Science Untuk Mempersiapkan Era Digital Pada Siswa Di SMAN 1 Gunung Sari - Dina Eka Putri; Baskara, Zulhan; Lisa Harsyiah; Agus Kurnia; Nur Asmita Purnamasari; Mustika Hadijati; Lilik Hidayati; Helmina Andriani; Jihadil Qudsi; Hafizah Ilma; Adis Tia Juli Agil Asri; Yuliana Lestari; Jihan Melani; Rifdah Fadhilah; M. Syahrul; M. Naoval Husni (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The Fourth Industrial Revolution and Society 5.0 have created a demand for technology-based skills, including Data Science. This community service program aimed to introduce Data Science concepts to students at SMAN 1 Gunung Sari, preparing them for the digital era. Through interactive training sessions covering Data Science basics, data analysis simulations, and career discussions, both students and teachers gained essential foundational knowledge. The results showed an increase in students' knowledge and motivation towards STEM fields, as well as new skills for teachers in integrating data-driven learning. This program also strengthened the school's profile as an institution proactive in preparing students for future technological challenges.